Analytical gradients for MP2, double hybrid functionals, and TD-DFT with polarizable embedding described by fluctuating charges - Carnimeo, Ivan (Journal of computational chemistry, 2015)
© 2015 The Authors. Journal of Computational Chemistry Published by Wiley Periodicals, Inc.